2018
DOI: 10.5144/0256-4947.2018.260
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of continuous renal replacement therapy in critically ill children: a retrospective cohort study

Abstract: BACKGROUNDContinuous renal replacement therapy (CRRT) has become the preferred mode of dialysis to support critically ill children with acute kidney injury. However, there are limited pediatric data on CRRT use, especially in our region.OBJECTIVEDetermine the outcome of CRRT among critically ill children.DESIGNRetrospective cohort study.SETTINGPediatric intensive care unit.PATIENTS AND METHODSThe study included critically ill children 1–14 years of age who underwent CRRT from July 2009 to June 2015. We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…Based on the clinical records, the most common underlying diseases leading to RRT in the current study were diabetes (36.9%) and hypertension (25.8%). These results were consistent with the reports of other studies indicating hypertension and diabetes as the underlying causes of RRT in 36.4% to 62.1% of the cases (11,(32)(33)(34). In some multicenter studies in children, malignancy has been reported as the most common primary diagnosis in patients requiring RRT (11).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Based on the clinical records, the most common underlying diseases leading to RRT in the current study were diabetes (36.9%) and hypertension (25.8%). These results were consistent with the reports of other studies indicating hypertension and diabetes as the underlying causes of RRT in 36.4% to 62.1% of the cases (11,(32)(33)(34). In some multicenter studies in children, malignancy has been reported as the most common primary diagnosis in patients requiring RRT (11).…”
Section: Discussionsupporting
confidence: 93%
“…These results were consistent with the reports of other studies indicating hypertension and diabetes as the underlying causes of RRT in 36.4% to 62.1% of the cases (11,(32)(33)(34). In some multicenter studies in children, malignancy has been reported as the most common primary diagnosis in patients requiring RRT (11). Overall, special attention must be dedicated to diabetes and hypertension as the main comorbidities leading to RRT.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations